Heat Shock Protein 60 in Vascular Biology : HSP60 in the Vasculature - Hedley, Thomas E; Deniset, Justin F; Francis, Andrew A; Pierce, Grant N (Scripta Medica, 2025)
The response of heat shock proteins (HSPs) to stress-induced stimuli is now well documented and understood. Specific HSPs like HSP70 play an important role in vascular diseases like atherosclerosis and hypertension. However, the involvement of other HSPs in these vascular pathologies has been largely ignored. HSP60 plays a particularly critical role in vascular cell growth, an important component of many vascular pathologies. HSP60 directly induces vascular smooth muscle cell proliferation. The mechanism may involve an HSP60-induced stimulation of the rate of nuclear protein import in the smooth muscle cell. HSP60 expression levels also correlate with the severity of the disease. In conclusion, HSP60 may have an important role to play in vascular diseases like atherosclerosis. HSP60 may be a promising future pharmaceutical target to focus upon in order to deter the pathological effects of disease conditions like hypertension and atherosclerosis.